CULTURE SHOCK DAN ADAPTASI MAHASISWA SUMATERA DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Isnia Septarini, Dinda; Widiyowati, Estu (Solidaritas, 2025)
This study aims to understand the phenomenon of culture shock experienced by migrant students from Sumatra at Slamet Riyadi University, Surakarta and to describe their adaptation efforts in overcoming the challenges of cross-cultural communication. The method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that Sumatran students have difficulty adapting to differences in language, communication patterns, food, and weather in Surakarta. However, students are able to adapt by learning the local language, mingling with the local community, and participating in social activities. This study emphasizes the importance of intercultural communication in the adaptation process of migrant students. This study also aims to contribute to the understanding of the dynamics of cross-cultural social interaction in higher education environments. Keywords: culture shock, intercultural communication, cultural adaptation, Sumatran